Imla’ Errors in Junior High School Students’ Writing: Criticism of Teacher's Pronunciation Error - Anggun Maharani, Khayyu; El Qorny, Ashief; Zainab Apriani, Rambu; Hilmi Syukri, Muhammad; Azis Wildani, Farhan (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
The number of errors that occur in students' Arabic wordswriting was one of the strongest reasons for researchers to research and analyze students' mistakes in writing Arabic. The teacher's unclear pronunciation can be one of the biggest factors in the occurrence of errors in students' Arabic writing. The researcher aimed to find out and analyze the errors and the various causal factors in writing student disclaimers. A qualitative descriptive research method was used in the research. Then, observation, interviews and documentation were carried our as data collection at junior boarding school in Yogyakarta. In the data analysis, data reduction, data presentation and data verification were used. Based on the data collected and analyzed, it was found that there was a teacher's pronunciationerrors in the dictation that causederrors in students’ writing which was described as follows; 1) the teacher's makhorijul hurufare not fluent and clear, 2) they are not careful in pronouncing vowels and mad (long and short rules), 3) the pronunciation of alif lam qomariyah and syamsiyah is not clear. From the results of this analysis, it can be proven that the pronunciation of a teacher in conveying dictation lessons greatly influences the results of students' writing dictation. This study providesd suggestions for teachers who will deliver dictation lessons.